P-Glycoprotein and Breast Cancer Resistance Protein in Canine Inflammatory and Noninflammatory Grade III Mammary Carcinomas. Issue 6 (November 2019) - Levi, Michela; Peña, Laura; Alonso-Díez, Angela; Brunetti, Barbara; Muscatello, Luisa Vera; Benazzi, Cinzia; Pérez-Alenza, Maria Dolores; Sarli, Giuseppe
P-glycoprotein (P-gp/ABCB1) and breast cancer resistance protein (BCRP/ABCG2) expression are frequently related to multidrug resistance (MDR) in neoplastic cells. Canine inflammatory and grade III noninflammatory mammary carcinomas (IMC and non-IMC) are aggressive tumors that could benefit from chemotherapy. This study describes the immunohistochemical detection of P-gp and BCRP in 20 IMCs and 18 non-IMCs from dogs that had not received chemotherapy. Our aim was to determine if P-gp and BCRP expression was related to the "inflammatory" phenotype, to establish a basis for future studies analyzing the response to chemotherapy in dogs with highly malignant mammary cancer. Immunolabeling was primarily membranous for P-gp with a more intense labeling in emboli, and immunolabeling was membranous and cytoplasmic for BCRP. P-gp was expressed in 17 of 20 (85%) IMCs compared to 7 of 18 (39%) non-IMCs ( P = 0.006). BCRP was expressed within emboli in 15 of 19 (79%) emboli in IMC, 12 of 15 (80%) primary IMCs, and 12 of 18 (67%) non-IMCs, without statistically significant differences ( P > .05). All IMCs and 67% of non-IMCs expressed at least 1 of the 2 transporters, and 63% (12/19) of IMCs and 39% (7/18) of non-IMCs expressed both P-gp and BCRP. P-gp and BCRP evaluation might help select patients for chemotherapy. P-gp, expressed in a significantly higher percentage of IMCs vs non-IMCs, might play a specific role in the chemoresistance of IMC.